Indications for biopsy and the current status of focal therapy for renal tumours - Leão, Ricardo R.N. (Transl Androl Urol, 2015)
The increased detection of small renal masses (SRMs) has focused attention on their uncertain natural history. The development of treatment alternatives and the discovery of biologically targeted drugs have also raised interest. Renal mass biopsies (RMBs) have a crucial role as they provide the pathological, molecular and genetic information needed to classify these lesions and guide clinical management. The improved accuracy has improved our knowledge of the behaviour of different tumour histologies and opened the potential for risk-adapted individualized treatment approaches. To date, studies have demonstrated that percutaneous ablation is an effective therapy with acceptable outcomes and low risk in the appropriate clinical setting. Although partial nephrectomy (PN) is still considered the standard treatment for SRM, percutaneous ablation is increasingly being performed and if long-term efficacy is sustained, it may have a wider application for SRMs after biopsy characterization.